Effects of semi-refined carrageenan (food additive E407a) on cell membranes of leukocytes assessed in vivo and in vitro - Tkachenko, A. S.; Onishchenko, A.; Roshal, Alexander; Nakonechna, O.; Chumachenko, T.; Posokhov, Ye. O. (My University, 2021)
No noticeable changes in the physico-chemical properties were observed in the lipid membranes of leukocytes in the region where the probes locate in response to oral intake of semi-refined carrageenan. Incubation of leukocytes with E407a solutions resulted in a decrease in polarity and proton-donor ability of leukocytes in the area of carbonyl groups of phospholipids and in the area of hydrocarbon chains of phospholipids near the polar region of the bilayer.
Keywords: fluorescence; membrane fluidity; phospholipids; polysaccharides; rats